Determinant Factors of Work Engagement in South - Viljoen, Salmari (My University, 2011)
The healthcare industry in South Africa has been subject to legislative changes in recent years that have impacted the pharmaceutical industry. Retail pharmacies are especially negatively affected with the new pricing regulations. In light of this, the research focuses on retail pharmacists. The purpose of this research is to identify the determinant factors of work engagement in South African retail pharmacists, and to measure the impact of the determinant factors on work engagement in South African retail pharmacists. A survey was conducted on a sample of retail pharmacists in South Africa, and the data was analysed quantitatively. An adapted version of May, Gilson & Harter’s (2004) model was used to test the determinant factors of work engagement. The results revealed that the determinant factors for this sample exhibited significant positive relations with work engagement, as well as influencing work engagement directly. The determinant factors identified were supervisor relations, resources, work role fit, co-worker relations, job enrichment and skill variety. Work role fit and co-worker relations influenced work engagement the most. The theoretical and practical implications related to work engagement are discussed
MBA - WBS
Keywords: Pharmacies; Healthcare sector